Implementasi Konsep Penologi Dan Panitensier Dalam Sistem Pemasyarakatan Di Indonesia - Aziza Nandhita; Nabila Fitriani; Asep Suherman (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
Penology and panitentiary are branches of criminal law that study the objectives of punishment and the rehabilitation system for criminal offenders. In the Indonesian legal context, these concepts are reflected in the correctional system, which aims not only to impose punishment but also to provide rehabilitation so that inmates can reintegrate into society. This article aims to analyze the implementation of the concepts of penology and panitentiary in the Indonesian correctional system. The method used in this paper is normative legal research with a statutory and conceptual approach. The results of the study indicate that the Indonesian correctional system has essentially adopted the principles of penology and panitentiary, which emphasize rehabilitation, rehabilitation, and social reintegration for inmates. However, in practice, various obstacles remain, such as limited facilities and infrastructure, overcrowding in correctional institutions, and limited optimal rehabilitation programs. Therefore, efforts are needed to improve the quality of the correctional system so that the goals of humanistic and rehabilitation-oriented punishment can be effectively achieved.